Evaluation of Safe Kids Week 2004: Age 4 to 9? It's Booster Seat Time!. Issue 5 (3rd October 2006) - Howard, A; Beben, N; Rothman, L; Fiissel, D; MacArthur, C
Abstract : Objective: To assess the effectiveness of a national one week media campaign promoting booster seat use. Design: Pre-test, post-test design based on nationally representative random digit dialing telephone survey, with control for exposure to campaign. Setting: Canada. Subjects: Parents of children aged 4–9 years. Interventions: During a one week campaign in May 2004, information on booster seat use was distributed via a national media campaign, retail stores, medical clinics, and community events. Information included pamphlets with guidelines for booster seat use, as well as a growth chart (designed by Safe Kids Canada) to assist parents in determining if their child should be using a booster seat. Assessing seat belt fit was described in detail on the growth chart. Main outcome measures: Knowledge, attitudes, and self-reported behaviors regarding booster seat use. Results: Respondents in the group exposed to the campaign were twice as likely to report using a booster seat with lap and shoulder belt for their child (47%), compared to those in the pre-test (24%) and the unexposed (23%) groups (p<0.001). However, only small differences in general knowledge regarding booster seat use were found between the groups. Conclusions: A one week national media campaign substantially increased self-reported use of booster seats. Parents did not remember details of the campaign content, but did remember implications for their own child.